The Wingless planar cell polarity pathway is essential for optimal activity-dependent synaptic plasticity - Dominicci-Cotto, Carihann; Vazquez, Mariam; Marie, Bruno (Frontiers in Synaptic Neuroscience, 2024)
From fly to man, the Wingless (Wg) / Wnt signaling molecule is essential for both the stability and plasticity of the nervous system. The Drosophila neuromuscular junction (NMJ) has proven to be a useful system for deciphering the role of Wg in directing activity-dependent synaptic plasticity, which, in the motoneuron, has been shown to be dependent on both the canonical and the noncanonical calcium Wg pathways. Here we show that the noncanonical planar cell polarity (PCP) pathway is an essential component of the Wg signaling system controlling plasticity at the motoneuron synapse. We present evidence that disturbing the PCP pathway leads to a perturbation in activity-dependent synaptic plasticity (ADSP). We first show that a PCP-specific allele of dishevelled (dsh) affects the de novo synaptic structures produced during ADSP. We then show that the Rho GTPases downstream of Dsh in the PCP pathway are also involved in regulating the morphological changes that take place after repeated stimulation. Finally, we show that Jun kinase is essential for this phenomenon, whereas we found no indication of the involvement of the transcription factor complex AP1 (Jun/Fos). This work shows the involvement of the neuronal PCP signaling pathway in supporting ADSP. Because we find that AP1 mutants can perform ADSP adequately, we hypothesize that, upon Wg activation, the Rho GTPases and Jun kinase are involved locally at the synapse, in instructing cytoskeletal dynamics responsible for the appearance of the morphological changes occurring during ADSP.